EVE, THE EXISTING ABJECT (Postmodern Feminist Study toward the Story of Adam and Eve in Bible) - Qurrota Ayunin (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The search for human creation story is very interesting to discuss if it is viewed with a different perspective from mainstream story. The story of human creation is commonly called the story of Adam and Eve. Often, the story we hear is implicated in the marginalization of woman through Eve because she was created from Adam’s ribs, and she was the cause of Adam’s sin by eating fruit which was forbidden by God. The story is confirmed in the Bible so that it can give rise to biased interpretations. This study will offer another perspective in reading the stories of Adam and Eve written in the scriptures from Genesis 2 and 3. The postmodern feminist theory will be employed in rereading the figure of Eve in the Bible. The idea of this theory is that Liyan as a way to exist. Hence, the figure of Eve is attributed to the figure of Liyan who has the ability to exist. Analysis of this Eve figure will be focused on Julia Kristeva’s view of the abject concept. Eventually, the concept of abject and Liyan stated in the postmodern feminist converged on the view that exclusion or non-existence is not entirely oppression which lead to the weakness figure. This is very closely related to the figure of Eve in the Bible so that the attribution in this study will lead to how Eve is seen as an existing abject. The result of this study reveals that Eve cannot be seen simply by focusing on her weaknesses by failing to maintain a commitment not to violate God’s rules. Yet, her negligence becomes an opening for knowledge. Eve’s negligence has manifested the world we currently live in as well. Holy books should be read with a variety of more egalitarian and unbiased perspectives so that gender justice can be realized without the pretext of religion as a barrier.